The Golgin Protein Giantin Regulates Interconnections Between Golgi Stacks - Satoh, Ayano; Hayashi-Nishino, Mitsuko; Shakuno, Takuto; Masuda, Junko; Koreishi, Mayuko; Murakami, Runa; Nakamura, Yoshimasa; Nakamura, Toshiyuki; Abe-Kanoh, Naomi; Honjo, Yasuko; Malsam, Joerg; Yu, Sidney; et al. (Frontiers in Cell and Developmental Biology, 2019)
Golgins are a family of Golgi-localized long coiled-coil proteins. The major golgin function is thought to be the tethering of vesicles, membranes, and cytoskeletal elements to the Golgi. We previously showed that knockdown of one of the longest golgins, Giantin, altered the glycosylation patterns of cell surfaces and the kinetics of cargo transport, suggesting that Giantin maintains correct glycosylation through slowing down transport within the Golgi. Giantin knockdown also altered the sizes and numbers of mini Golgi stacks generated by microtubule de-polymerization, suggesting that it maintains the independence of individual Golgi stacks. Therefore, it is presumed that Golgi stacks lose their independence following Giantin knockdown, allowing easier and possibly increased transport among stacks and abnormal glycosylation. To gain structural insights into the independence of Golgi stacks, we herein performed electron tomography and 3D modeling of Golgi stacks in Giantin knockdown cells. Compared with control cells, Giantin-knockdown cells had fewer fenestrae within each cisterna. This was supported by data showing that the diffusion rate of Golgi membrane proteins is faster in Giantin-knockdown Golgi, indicating that Giantin knockdown structurally and functionally increases connectivity among Golgi cisternae and stacks. This increased connectivity suggests that contrary to current understanding, Giantin instead inhibits the tether and fusion of nearby Golgi cisternae and stacks, resulting in transport difficulties between stacks that may enable the correct glycosylation of proteins and lipids passing through the Golgi.